Playing as if the world mattered : an illustrated history of activism in sports - Kuhn, Gabriel (Oakland, CA PM Press, 2015)
The world of sports is often associated with commercialism, corruption, and reckless competition. Liberals have objected to sport being used for political propaganda, and leftists have decried its role in distracting the masses from the class struggle. Yet, since the beginning of organized sports, athletes, fans, and officials have tried to administer and play it in ways that strengthen, rather than hinder, progressive social change. From the workers' sports movement in the early 20th century to the civil rights struggle transforming sports in the 1960s to the current global network of grassroots sports clubs, there has been a glowing desire to include sports in the struggle for liberation and social justice. With the help of numerous full-color illustrations--from posters and leaflets to paintings and photographs-- Playing as if the World Mattered makes this history tangible and introduces an understanding of sports beyond chauvinistic jingoism, corporate-media chat rooms, and multibillion-dollar business deals.
Keywords: Sports and society -- History; Sports -- Political aspects